Pengaruh Café Atmosphere dan Service Quality terhadap Keputusan Pembelian di Kalenan Café and Resto Sawahan Kabupaten Nganjuk - Linda Puspitasari; Dwi Puji Rahayu; Muhammad Bawono (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of Café Atmosphere and Service Quality on Purchase Decision at Kalenan Café and Resto, Sawahan District, Nganjuk Regency. The independent variables in this research are Café Atmosphere (X₁) and Service Quality (X₂), while the dependent variable is Purchase Decision (Y). This research employs a quantitative method with a causal associative approach. Data were collected by distributing questionnaires to 99 respondents who had previously made purchases at Kalenan Café and Resto. The results indicate that partially, Café Atmosphere (X₁) has a significant influence on Purchase Decision with a significance value of 0.002, and Service Quality (X₂) also has a significant influence with a significance value of 0.000. Simultaneously, Café Atmosphere and Service Quality significantly affect Purchase Decision with a significance value of 0.000 and an F-value of 14.111. Therefore, it can be concluded that the café’s atmosphere and service quality are essential factors that must be considered by management to increase consumers’ purchase decisions.